Hydration of the RNA duplex r(CGCAAAUUUGCG)2 determined by NMR. - Conte, MR; Conn, G; Brown, T; Lane, A (1996)
The so-called spine of hydration in the minor groove of AnTn tracts in DNA is thought to stabilise the structure, and kinetically bound water detected in the minor groove of such DNA species by NMR has been attributed to a narrow minor groove [Liepinsh, E., Leupin, W. and Otting, G. (1994) Nucleic Acids Res. 22, 2249-2254]. We report here an NMR study of hydration of an RNA dodecamer which has a wide, shallow minor groove. Complete assignments of exchangeable protons, and a large number of non-exchangeable protons in r(CGCAAAUUUGCG)2 have been obtained. In addition, ribose C2'-OH resonances have been detected, which are probably involved in hydrogen bonds. Hydration at different sites in the dodecamer has been measured using ROESY and NOESY experiments at 11.75 and 14.1 T. Base protons in both the major and minor grooves are in contact with water, with effective correlation times for the interaction of approximately 0.5 ns, indicating weak hydration, in contrast to the hydration of adenine C2H in the homologous DNA sequence. NOEs to H1' in the minor groove are consistent with hydration water present that is not observed in the analogous DNA sequence. Hydration kinetics in nucleic acids may be determined by chemical factors such as hydrogen-bonding more than by simple conformational factors such as groove width.